Pajak Penghasilan Pada Subjek Penghasilan Di Bawah Umur Melalui Media Sosial - Sari Dewi, Retno (Fakultas Hukum, Universitas Muslim Indonesia, 2020)
The unregulated income tax for underage tax subjects who use social media in Indonesia needs attention from the government. The increasing number of social media users by underage tax subjects who currently do not receive supervision. The self-assessment-based income tax collection system is also an obstacle to this problem. In the study in this article using the socio-legal research method which examines the limitations of legal sources. Normative aspects and often legal issues are related to social and political contexts in empirical aspects. The findings from this study required policy formulation: mapping data on underage tax subjects with income generation using social media content, collaborating with various related parties and conducting a review of the income tax collection system.